Taking the Charisma Out: Teaching as Facilitation - Joseph A. Raelin (Organization Management Journal, 2006)
The author provides a personal account of his transition from attempting to use charisma to transmit knowledge to students to removing it so that students can themselves experience knowledge as a basis for learning. Consistent with inquiry-based democratic pedagogy, the author demonstrates how he became more a facilitator of learning than its transmitter. He shows how putting charisma into unscheduled classroom inquiry rather than into the teacher's delivery can produce knowledge collectively and concurrently co-constructed in service of action.
Keywords: I20; J24; L20; M10; M12; M14; M53; M50; O31; O15; 330; Facilitation; Charisma; Reflective practice; Inquiry; Higher education